2018
DOI: 10.1111/jvim.14903
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Oral Administration of Sodium Iodide to Prevent Bovine Respiratory Disease Complex

Abstract: BackgroundThe prevention of bovine respiratory disease complex (BRD) in beef cattle is important to maintaining health and productivity of calves in feeding operations.ObjectiveDetermine whether BRD bacterial and viral pathogens are susceptible to the lactoperoxidase/hydrogen peroxide/iodide (LPO/H2O2/I−) system in vitro and to determine whether the oral administration of sodium iodide (NaI) could achieve sufficient concentrations of iodine (I) in the respiratory secretions of weaned beef calves to inactivate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
1
13
0
Order By: Relevance
“…Even after a single dose of 70 mg NaI, iodide levels did not achieve baseline even on day 3. At the same time, the effectiveness of the action of iodides was against Mannheimia haemolytica and Bibersteinia trehalosi insignificant at concentrations of 500 μM and below [19]. Only when combined with an antibiotic is a significant effect achieved.…”
Section: Resultsmentioning
confidence: 87%
“…Even after a single dose of 70 mg NaI, iodide levels did not achieve baseline even on day 3. At the same time, the effectiveness of the action of iodides was against Mannheimia haemolytica and Bibersteinia trehalosi insignificant at concentrations of 500 μM and below [19]. Only when combined with an antibiotic is a significant effect achieved.…”
Section: Resultsmentioning
confidence: 87%
“…The antimicrobial effects of hypohalous acids such as HOI on enveloped viruses is variable and unpredictable. Although the few in vivo experiments of iodine supplementation in sheep or cattle infected with respiratory viruses have yielded promising results, the pathogenic microorganisms tested did not include coronaviruses 5,30,31 . Patel et al measured a K i of ~10 µM for in uenza viruses for HOI generated in vitro 6 .…”
Section: Discussionmentioning
confidence: 99%
“…However, experimentally, the substitution of SCN − by I − increases the innate antiviral defences of the respiratory mucosa against adenoviruses and the respiratory syncytial virus ( 81 ). Oral administration of KI vs. NaI increases iodemia, allowing for the accumulation of I − in the mucous secretions of the upper respiratory tract in humans ( 81 ) as well as animals ( 82 , 83 ). Although it has already been demonstrated that I − accumulates in submandibular glands in hamsters ( 84 ), no similar observations have been reported in humans.…”
Section: Oxidant Production By Oral Peroxidasesmentioning
confidence: 99%